'Un-certainty': working therapeutically with a transgender young person and learning to bear the unknown. Issue 1 (2nd January 2018) - Tsoukala, Konstantina
Abstract: The rate of referrals to mental health services for children and young people for whom gender dysphoria is the identified clinical issue has increased significantly over the last ten years. Debates around the classifications of gender identity disorder, gender dysphoria or gender incongruence, as well as the involvement of child and adolescent mental health services with this group of children and young people seem to be re-enacting the societal gender binary world view where we see acceptance versus rejection, open-mindedness versus conservative, trans-phobic thinking. In this paper the author will attempt to shed some light on the work with these young people in a clinical setting by reflecting on a year of therapeutic work with a female to male young person. Through the therapist's reflections upon these binary preconceptions, along with the use of developmental and object relations theory, an in-depth account of the work is given. It is suggested that in some cases the therapist's capacity to bear the unknown, while gradually observing and mirroring the un-integrated inner self of the patient, can gradually bring the fragments together, even if not in a perfect fit, and that this in turn provides a sense of relief.